2017
DOI: 10.3389/fpls.2017.00895
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of MIKCc-Type MADS-Box Genes in Gymnosperms and Angiosperms

Abstract: MIKCc-type MADS-box genes encode transcription factors that control floral organ morphogenesis and flowering time in flowering plants. Here, in order to determine when the subfamilies of MIKCc originated and their early evolutionary trajectory, we sampled and analyzed the genomes and large-scale transcriptomes representing all the orders of gymnosperms and basal angiosperms. Through phylogenetic inference, the MIKCc-type MADS-box genes were subdivided into 14 monophyletic clades. Among them, the gymnosperm ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 29 publications
6
40
2
Order By: Relevance
“…Phylogenetic analysis revealed that these ten genes were highly conserved evolutionarily. However, no AP1/FUL (A-type genes) subfamily genes were identi ed in this study, and the number of MIKC-type MADS-box genes was lower in L. chinense less than in A. thaliana, P. trichocarpa and Amborella trichopoda [94]. In actuality, L. chinense originated earlier than A. thaliana and P. trichocarpa but later than A. trichopoda, and in angiosperms, the number of ABCE-type genes has increased [7,94].…”
Section: Discussioncontrasting
confidence: 55%
“…Phylogenetic analysis revealed that these ten genes were highly conserved evolutionarily. However, no AP1/FUL (A-type genes) subfamily genes were identi ed in this study, and the number of MIKC-type MADS-box genes was lower in L. chinense less than in A. thaliana, P. trichocarpa and Amborella trichopoda [94]. In actuality, L. chinense originated earlier than A. thaliana and P. trichocarpa but later than A. trichopoda, and in angiosperms, the number of ABCE-type genes has increased [7,94].…”
Section: Discussioncontrasting
confidence: 55%
“…Then, FastTree software was used to establish phylogenetic tree using 1,000 resamples, and constructed by maximum-likelihood using the JTT + CAT model. FastTree provides local support values by the Shimodaira-Hasegawa (SH) test, the resulting support values were closely correlated with the traditional bootstrap ( r = 0.975) ( Price et al, 2010 ; Chen et al, 2017 ). The local support values below 60 are hidden in the constructed tree.…”
Section: Methodsmentioning
confidence: 88%
“…The recent genome comparisons indicate that male ‘BC’ and female ‘C’ systems already existed to specify reproductive cells in gymnosperm cones, and they were duplicated via the ε WGD, after which the C duplicates diversified into angiosperm C and D genes. An A/E gymnosperm pro-orthologue gave rise to angiosperm A and E genes, and further duplicated A genes were also retained after the ε WGD 19 , 21 24 . These duplicated and diversified gene sets organised to generate the first now-extinct flowers, and recent reconstructions suggest that these were bisexual with petal-like tepals and pollen-bearing stamens arranged in multiple concentric whorls, and female carpels in a central spiral 25 .…”
Section: Contributions Of Whole-genome Duplications To the Origin Andmentioning
confidence: 99%